Determinan Kualitas Audit Berdasarkan Perspektif Keperilakuan - Sari, Ratna Novita; Indira Januarti (Politeknik Ganesha Medan, 2024)
This examination seeks to analyze and present empirical evidence regarding the influence of ethics, professionalism, and dysfunctional audit behavior on audit quality. A quality audited financial report is the basis for users of financial reports in making decisions. The research sample was auditors at public accounting firms in the provinces of West Java, Central Java, and East Java registered in the Directory of the Indonesian Institute of Public Accountants with a total of 162 auditors. The sampling technique is convenience sampling or sampling based on data availability. This research is quantitative research with data collection using a questionnaire. The questionnaire used utilizes Google Form because it makes it easier to send the questionnaire to each public accounting firm's email. The analysis tool uses multiple linear regression with IBM SPSS 26 software. Research findings show that auditor ethics and auditor professionalism have a positive effect on audit quality. This indicates that the higher the auditor's ethics and professionalism, the higher the quality of the resulting audit. In contrast, dysfunctional audit behavior does not show a significant negative influence on audit quality. These results indicate that the presence or absence of dysfunctional audit behavior cannot be the cause of the quality of the financial statement audit